2022
DOI: 10.3389/fphar.2022.952441
|View full text |Cite
|
Sign up to set email alerts
|

Evidence basis for using dexmedetomidine to enhance the quality of paravertebral block: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background: Dexmedetomidine is considered an adjunct to local anaesthesia (LA) to prolong peripheral nerve block time. However, the results from a previous meta-analysis were not sufficient to support its use in paravertebral block (PVB). Therefore, we performed an updated meta-analysis to evaluate the efficacy of dexmedetomidine combined with LA in PVB.Methods: We performed an electronic database search from the date of establishment to April 2022. Randomized controlled trials (RCTs) investigating the combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…19,21 This study revealed that compared with ropivacaine alone, perineural or IV dexmedetomidine can reduce VAS scores at rest and movement and Prince-Henry Pain scores at 12 and 24-h after surgery, and reduce the consumption of intraoperative and postoperative OME, which was consistent with previous studies. 40 QoR-15 is a validated quality assessment tool, and the results demonstrated that perineural and IV dexmedetomidine can improve the QOD-15 score at POD1 compared with ropivacaine alone, which has achieved minimum clinically important difference (MCID) (6.0). 41 Another important result of our study was the effect of perineural dexmedetomidine compared to IV dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 This study revealed that compared with ropivacaine alone, perineural or IV dexmedetomidine can reduce VAS scores at rest and movement and Prince-Henry Pain scores at 12 and 24-h after surgery, and reduce the consumption of intraoperative and postoperative OME, which was consistent with previous studies. 40 QoR-15 is a validated quality assessment tool, and the results demonstrated that perineural and IV dexmedetomidine can improve the QOD-15 score at POD1 compared with ropivacaine alone, which has achieved minimum clinically important difference (MCID) (6.0). 41 Another important result of our study was the effect of perineural dexmedetomidine compared to IV dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%